1995
DOI: 10.21273/jashs.120.3.374
|View full text |Cite
|
Sign up to set email alerts
|

St. Augustinegrass Rooting following Preemergence Herbicide Application

Abstract: Greenhouse studies were conducted at the Univ. of Florida to evaluate the effects of preemergence herbicides on St. Augustinegrass [Stenotaphrum secundatum (Walt.) Kuntze] rooting. Metolachlor, atrazine, metolachlor + atrazine, isoxahen, pendimethalin, dithiopyr, and oxadiazon were applied to soil columns followed by placement of St. Augustinegrass sod on the treated soil. Root elongation and biomass were measured following application. Plants treated with dithiopyr and pendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…dithiopyr can limit the root development of St. Augustinegrass plugs, thereby decreasing their ability to absorb water and nutrients (McCarty et al, 1995b). Results presented here, and those of others, suggest that prodiamine, pendimethalin, and dithiopyr, even when applied at labeled rates, can negatively impact St. Augustinegrass establishment from plugs.…”
Section: T a B L Esupporting
confidence: 55%
See 2 more Smart Citations
“…dithiopyr can limit the root development of St. Augustinegrass plugs, thereby decreasing their ability to absorb water and nutrients (McCarty et al, 1995b). Results presented here, and those of others, suggest that prodiamine, pendimethalin, and dithiopyr, even when applied at labeled rates, can negatively impact St. Augustinegrass establishment from plugs.…”
Section: T a B L Esupporting
confidence: 55%
“…Prodiamine, pendimethalin, and dithiopyr target microtubule assembly thus inhibiting root elongation (Appleby & Valverde, 1989; Armbruster et al., 1991). The application of prodiamine, pendimethalin, and dithiopyr can limit the root development of St. Augustinegrass plugs, thereby decreasing their ability to absorb water and nutrients (McCarty et al., 1995b). Results presented here, and those of others, suggest that prodiamine, pendimethalin, and dithiopyr, even when applied at labeled rates, can negatively impact St. Augustinegrass establishment from plugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taylor et al (2004) reported carfentrazone treatments caused acceptable injury to actively growing St. Augustinegrass on all dates evaluated. McCarty et al (1995) noted St. Augustinegrass sod root biomass was not inhibited when planted in soil treated with oxadiazon at 1.7 and 3.4 kg ha À1 . St. Augustinegrass appears sensitive to flumioxazin during active growth, but applications at , 25% green cover may have potential safety.…”
Section: Resultsmentioning
confidence: 90%